A New Device for Endovascular Coil Retrieval from Intracranial Vessels: Alligator Retrieval Device - Henkes, H.; Lowens, S.; Preiss, H.; Reinartz, J.; Miloslavski, E.; Kühne, D. (American Journal of Neuroradiology, 2006)
SUMMARY: The clinical use of a new device (Alligator Retrieval Device) designed specifically for endovascular foreign body (eg, coils) retrieval from intracranial vessels is reported. The Alligator has intrinsic advantages compared with microsnares for the endovascular catheter-based removal of coils.